The Role of Language in Alexithymia: Moving Towards a Multiroute Model of Alexithymia. (July 2019) - Hobson, Hannah; Brewer, Rebecca; Catmur, Caroline; Bird, Geoffrey
Alexithymia is characterized by difficulty identifying and describing one's own emotion. Identifying and describing one's emotion involves several cognitive processes, so alexithymia may result from a number of impairments. Here we propose the alexithymia language hypothesis—the hypothesis that language impairment can give rise to alexithymia—and critically review relevant evidence from healthy populations, developmental disorders, adult-onset illness, and acquired brain injury. We conclude that the available evidence is supportive of the alexithymia–language hypothesis, and therefore that language impairment may represent one of multiple routes to alexithymia. Where evidence is lacking, we outline which approaches will be useful in testing this hypothesis.